Analisis dampak lingkungan budidaya ikan terhadap kondisi lingkungan di Kelurahan Panaikang Kecamatan Panakukang Kota Makassar - Febrianti, Haswina; Ifa, La; Yani, Setyawati (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to analyze the environmental impacts of fish farming activities on the surrounding environment, particularly on the Tallo River and nearby residential areas. The environmental impact assessment focused on water and air quality across various aquaculture sites. Water quality was analyzed through in-situ and ex-situ sampling at four distinct points: Station 1 (upstream of the Tallo River), Station 2 (discharge outlet from aquaculture ponds into the Tallo River), Station 3 (downstream of the Tallo River), and Station 4 (wells within the Panaikang residential area). Three parameters were evaluated: physical (temperature, odor, and color), chemical (pH, DO, BOD, and COD), and biological (total coliform). While the physical and biological parameters met established standards, the chemical parameters fell below permissible thresholds. Specifically, DO, BOD, and COD values at Stations 2 and 3 revealed concerning levels: DO at 3.8 mg/L and 2.6 mg/L; BOD at 3.61 mg/L and 11.7 mg/L; and COD at 36.9 mg/L and 74.1 mg/L, respectively, indicating water pollution attributable to fish farming activities. Air quality assessments, including noise level measurements, were conducted at two points: Station 1 (within the aquaculture area) and Station 2 (Panaikang residential area). Noise levels were measured exclusively in the aquaculture zone. Results demonstrated compliance with regulatory standards for air quality and noise levels, indicating no significant risk of air pollution. A community survey further corroborated these findings, with 77% of respondents affirming that aquaculture activities did not disrupt their daily lives or environmental quality.